Emerging Trends in Cloud Computing - Tara, Deepti; Thakur, Pooja (Indian Journal of Computer Science, 2016)
As we are adopting internet technology in most of our day to day processes and it is considered to be somewhat more than a mere medium of communication, new technologies of distributed computing are emerging to take the businesses to a new platform. Cloud computing has become the hottest pick for practitioners and researchers. Everyone today is talking about cloud. A considerable amount of research has been done in this direction to identify the applications of cloud in businesses. Cloud computing is an umbrella term to define the services that are remotely hosted, always available from anywhere and are co-modified. Every IT industry is migrating to cloud to meet high computational requirement and that too at very low cost. This paper gives an idea of the services offered by cloud. A brief summary of the emerging services expected to be provided by cloud is also presented.Â 